Wavelet-Local binary pattern based face recognition - Ameen, Azad Abdullah; M-Saleh, Hardi M.; Abdul, Zrar Kh. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2017)
Over the last twenty years face recognition has made immense progress based on statistical learning or subspace discriminant analysis. This paper investigates a technique to reduce features necessary for face recognition based on local binary pattern, which is constructed by applying wavelet transform into local binary pattern. The approach is evaluated in two ways: wavelet transform applied to the LBP features and wavelet transform applied twice on the original image and LBP features. The resultant data are compared to the results obtained without applying wavelet transform, revealing that the reduction base one wavelet achieves the same or sometimes improved accuracy. The proposed algorithm is experimented on the Cambridge ORL Face database.